2014
DOI: 10.4103/0253-7176.135384
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Telepsychiatry in Maharashtra, India: Study of Feasibility and Referral Pattern

Abstract: Context:There is a paucity of published telepsychiatry results in India.Aims:This study was conducted to assess the feasibility of asynchronous telepsychiatry and to study the referral patterns.Settings and Design:This study was conducted in the telemedicine unit of a tertiary care center and design was retrospective analysis of 94 cases, which were diagnosed and treated by telepsychiatry.Materials and Methods:All 94 patients who were referred between January 2007 and August 2013 for telepsychiatry consultatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…15 In Chile, an online platform facilitated collaborative care by giving primary care providers remote access to a psychiatrist, which contributed to improved outcomes for care of people with depression. 16 In one study, 17 primary care providers from district hospitals in India sent patient reports to consulting psychiatrists at a tertiary medical centre to obtain treatment recommendations, whereas in another study from Pakistan, 18 reports on children or adolescents with complex presentations of mental illness were sent to psychiatrists in the UK for clinical guidance and feedback. Use of email to seek remote consultation from specialists is referred to as asynchronous or so-called store-and-forward telepsychiatry, 17,18 however, this approach seems to be an extension of existing practices of sending paper copies to consultants rather than an application of technology with potential for population-level impact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In Chile, an online platform facilitated collaborative care by giving primary care providers remote access to a psychiatrist, which contributed to improved outcomes for care of people with depression. 16 In one study, 17 primary care providers from district hospitals in India sent patient reports to consulting psychiatrists at a tertiary medical centre to obtain treatment recommendations, whereas in another study from Pakistan, 18 reports on children or adolescents with complex presentations of mental illness were sent to psychiatrists in the UK for clinical guidance and feedback. Use of email to seek remote consultation from specialists is referred to as asynchronous or so-called store-and-forward telepsychiatry, 17,18 however, this approach seems to be an extension of existing practices of sending paper copies to consultants rather than an application of technology with potential for population-level impact.…”
Section: Resultsmentioning
confidence: 99%
“…16 In one study, 17 primary care providers from district hospitals in India sent patient reports to consulting psychiatrists at a tertiary medical centre to obtain treatment recommendations, whereas in another study from Pakistan, 18 reports on children or adolescents with complex presentations of mental illness were sent to psychiatrists in the UK for clinical guidance and feedback. Use of email to seek remote consultation from specialists is referred to as asynchronous or so-called store-and-forward telepsychiatry, 17,18 however, this approach seems to be an extension of existing practices of sending paper copies to consultants rather than an application of technology with potential for population-level impact. Nonetheless, this method can afford benefit, as shown in a study from Colombia 19 in which asynchronous telepsychiatry was used to supplement primary care visits for depression treatment among prisoners.…”
Section: Resultsmentioning
confidence: 99%
“…In India, both synchronous (Agarwal et al, 2019;Das et al, 2020;Gowda et al, 2018) and asynchronous mode of video consultation (Balasinorwala et al, 2014) are in place since the last two decades (Chellaiyan et al, 2019). However, the utility has remained minimal as there were no guidelines and laws about the use of telemedicine in clinical practice.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Studies in Opioid dependence patients on medication assisted treatments have reported that there is no significant difference in the outcomes of patients treated with face to face consultations and through telepsychiatry, implying its potential role in the development of treatment services 39 . In India, asynchronous telepsychiatry had been seen as a feasible option 40 . Even though there has been expertise developed as well as research conducted in telepsychiatry in the area of general psychiatry, its applicability in addiction mental health has not been studied.…”
Section: Introductionmentioning
confidence: 99%